2015
DOI: 10.1021/acsmedchemlett.5b00049
|View full text |Cite
|
Sign up to set email alerts
|

Monocarboxylate Transporter 1 Inhibitors as Potential Anticancer Agents

Abstract: Potent monocarboxylate transporter 1 inhibitors (MCT1) have been developed based on α-cyano-4-hydroxycinnamic acid template. Structure−activity relationship studies demonstrate that the introduction of p-N, N-dialkyl/diaryl, and o-methoxy groups into cyanocinnamic acid has maximal MCT1 inhibitory activity. Systemic toxicity studies in healthy ICR mice with few potent MCT1 inhibitors indicate normal body weight gains in treated animals. In vivo tumor growth inhibition studies in colorectal adenocarcinoma (WiDr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
71
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(75 citation statements)
references
References 21 publications
1
71
3
Order By: Relevance
“…23 This transport inhibition study revealed carboxy coumarins 4a – 4e as potent inhibitors of MCT1 at nanomolar to low micromolar concentrations (Table 1). …”
mentioning
confidence: 89%
See 2 more Smart Citations
“…23 This transport inhibition study revealed carboxy coumarins 4a – 4e as potent inhibitors of MCT1 at nanomolar to low micromolar concentrations (Table 1). …”
mentioning
confidence: 89%
“…1922 Elevated expression of MCT1 has been identified in a large number of cancers and, therefore, this transporter is a major selective target for broad-spectrum cancer treatment. 2334 In this regard, we recently developed a series of MCT1 inhibitors based on the α-hydroxy-4-cyanocinnamic acid (CHC) template for potential anticancer applications. 23 Although our earlier CHC based MCT1 inhibitors are potent, the lead compounds suffer from poor oral bioavailability and toxicity at high concentrations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to tumor-stromal cell interactions, a critically important discovery was the demonstration that tumor cells can induce neighboring stromal cells to become glycolytic and release high energy compounds that fuel malignant cell growth, a process called the "reverse Warburg effect." Due to these activities, compounds expressing efficient inhibition of MCTs have been proposed and studied as potential chemotherapeutic agents (8). In this case, these cancerassociated fibroblasts undergo aerobic glycolysis to produce pyruvate and lactate, which are then transported by monocarboxylate transporters (MCT1 and MCT4) to growing cancer cells for further adenosine triphosphate (ATP) synthesis by the tricarboxylic acid (TCA) cycle and OXPHOS (2,(4)(5)(6).…”
mentioning
confidence: 99%
“…This stimulated production of new blood vessels can further support the proliferation of tumor cells by delivering oxygen and resources needed for cell growth. Due to these activities, compounds expressing efficient inhibition of MCTs have been proposed and studied as potential chemotherapeutic agents (8).…”
mentioning
confidence: 99%